2011
DOI: 10.1189/jlb.0310179
|View full text |Cite
|
Sign up to set email alerts
|

CD154-CD40 interactions in the control of murine B cell hematopoiesis

Abstract: CD154 is expressed by radioresistant cells in the bone marrow, and plays a role in fine-tuning B cell hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Numerous studies have shown that EAMG is CD4 + T cell‐dependent and requires the co‐stimulatory molecules CD40L and CD40 on T and B cells, respectively . Both CD80 and CD86 are necessary for T cell activation and survival, while the interaction between CD40 and its ligand (CD40L) can activate resting B cells and enhance the expression of CD80 and CD86 . It has been reported that a B7‐deficiency can result in lower titres of the virus‐specific IgG2a response and a lack of an IgG1 response in mice infected with the vesicular stomatitis virus .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that EAMG is CD4 + T cell‐dependent and requires the co‐stimulatory molecules CD40L and CD40 on T and B cells, respectively . Both CD80 and CD86 are necessary for T cell activation and survival, while the interaction between CD40 and its ligand (CD40L) can activate resting B cells and enhance the expression of CD80 and CD86 . It has been reported that a B7‐deficiency can result in lower titres of the virus‐specific IgG2a response and a lack of an IgG1 response in mice infected with the vesicular stomatitis virus .…”
Section: Discussionmentioning
confidence: 99%
“…The signal transduction mediated by CD40-CD40L interaction could activate NF-κB, STAT3, MAPK, and other kinases ( Van Kooten and Banchereau, 2000 ; Elgueta et al., 2009 ). Accumulated studies have indicated that CD40 is responsible for promoting cellular and humoral adaptive immunity and inflammatory responses ( Van Kooten and Banchereau, 2000 ; Benveniste et al., 2004 ; Elgueta et al., 2009 ; Carlring et al., 2011 ). Besides, interaction of CD40 and CD40L between the DCs and CD4 + T cells triggers DCs to activate cytotoxic CD8 + cells ( Bennett et al., 1998 ; Ridge et al., 1998 ; Schoenberger et al., 1998 ).…”
Section: Regulators In Anti-malaria Immune Responsesmentioning
confidence: 99%
“…CD40-mediated signal transduction activates multiple pathways, including those signaling through NFκB, STAT3 (Signal transducers and activators of transcription-3), MAPK (Mitogen-activated protein kinase), and other kinases [ 17 19 ]. CD40 is mostly known to function in the initiation and progression of cellular and humoral adaptive immunity, including T cell-dependent immunoglobulin class switching, memory B cell development, and germinal center formation [ 17 , 18 , 20 ]. Engagement of CD40 on macrophages and CD40L on T-cells has been shown to promote inflammatory responses in many neurologic diseases [ 21 ].…”
Section: Introductionmentioning
confidence: 99%